Foreign direct investment and total factor productivity growth: does distance from technology frontier matter?. (2016) - Roy, Subaran
We investigate the effects of the important channel of technology diffusion namely foreign direct investment (FDI) on the total factor productivity (TFP) growth. We contribute to the literature by empirically investigating the role of initial distance of a country from the technology frontier in determining the net effect of FDI on TFP growth. In this study, we find that the net effect of FDI on TFP growth decreases with the increase in distance. In order to take this research a step further, we implement the threshold regression technique to explore the nonlinearity associated with FDI. Our findings suggest that if initial distance of a country exceeds a threshold level then the leader will have a locomotive effect and can pull the followers along, while in the other situation there is a significant negative impact of FDI that increases with distance as a result of which the net benefit from FDI can be miniscule.